2012
DOI: 10.1097/aln.0b013e318247564d
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Environmental Enrichment Reverses Sevoflurane-induced Memory Impairment in Rats

Abstract: Background Anesthesia given to immature rodents causes cognitive decline raising the possibility that the same might be true for millions of children undergoing surgical procedures under general anesthesia each year. We tested the hypothesis that anesthesia-induced cognitive decline in rats is treatable. We also tested if anesthesia-induced cognitive decline is aggravated by tissue injury. Methods 7-day old rats underwent sevoflurane anesthesia (1 MAC, 4 hours) with or without tail clamping. At 4 weeks, rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
109
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 54 publications
6
109
4
Order By: Relevance
“…Previously, two groups conducted learning and memory behavioral tests on neonatal sevo‐treated rats without tail clamping (Shih et al. 2012; Stratmann et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, two groups conducted learning and memory behavioral tests on neonatal sevo‐treated rats without tail clamping (Shih et al. 2012; Stratmann et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Long treatment duration indicates potential physiologically intolerable toxicity; this resulted in decreased survival rates from 92% to 67% between the 2 and 4 h (Shih et al. 2012). The present study demonstrated for the first time a single‐episode, 2‐h treatment by sevo alone during the neonatal period impairs both social interaction and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has been observed to occur acutely in the period immediately following anesthesia (Jevtovic-Todorovic et al, 2003;Istaphanous et al, 2011;Shih et al, 2012), and the thalamus and hippocampus are known areas susceptible to extensive neurodegeneration (JevtovicTodorovic et al, 2003;Satomoto et al, 2009;Shih et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In rodent models, the effects of anesthesia have been evaluated following exposure during a time of peak brain development and synaptogenesis, typically at postnatal day 7 (P7) (Jevtovic-Todorovic et al, 2003;Stratmann et al, 2009b;Shih et al, 2012). Apoptosis has been observed to occur acutely in the period immediately following anesthesia (Jevtovic-Todorovic et al, 2003;Istaphanous et al, 2011;Shih et al, 2012), and the thalamus and hippocampus are known areas susceptible to extensive neurodegeneration (JevtovicTodorovic et al, 2003;Satomoto et al, 2009;Shih et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation